Molecular Characteristics of Novel Phage vB_ShiP-A7 Infecting Multidrug-Resistant Shigella flexneri and Escherichia coli, and Its Bactericidal Effect in vitro and in vivo - Xu, Jing; Zhang, Ruiyang; Yu, Xinyan; Zhang, Xuesen; Liu, Genyan; Liu, Xiaoqiu (Frontiers in Microbiology, 2021)
In recent years, increasing evidence has shown that bacteriophages (phages) can inhibit infection caused by multidrug-resistant (MDR) bacteria. Here, we isolated a new phage, named vB_ShiP-A7, using MDR Shigella flexneri as the host. vB_ShiP-A7 is a novel member of Podoviridae, with a latency period of approximately 35 min and a burst size of approximately 100 phage particles/cell. The adsorption rate constant of phage vB_ShiP-A7 to its host S. flexneri was 1.405×10-8 mL/min. The vB_ShiP-A7 genome is a linear double-stranded DNA composed of 40,058 bp with 177 bp terminal repeats, encoding 43 putative open reading frames. Comparative genomic analysis demonstrated that the genome sequence of vB_ShiP-A7 is closely related to 15 different phages, which can infect different strains. Mass spectrometry analysis revealed that 12 known proteins and 6 hypothetical proteins exist in the particles of phage vB_ShiP-A7. Our results confirmed that the genome of vB_ShiP-A7 is free of lysogen-related genes, bacterial virulence genes, and antibiotic resistance genes. vB_ShiP-A7 can significantly disrupt the growth of some MDR clinical strains of S. ﬂexneri and Escherichia coli in liquid culture and biofilms in vitro. In addition, vB_ShiP-A7 can reduce the load of S. ﬂexneri by approximately 3–10 folds in an infection model of mice. Therefore, vB_ShiP-A7 is a stable novel phage with the potential to treat infections caused by MDR strains of S. ﬂexneri and E. coli.